Speciation of Candida species isolated from cutaneous skin lesions using CHROMagar and conventional methods - Neha Rathore; Jaya Lalwani; Priyanka Singh; Mamta Meena (Asian Journal of Medical Sciences, 2024)
Background: Candida species are members of the normal flora of the skin, mucous membranes, and gastrointestinal tract. They are endogenous opportunists which cause secondary infection in individuals with some underlying immunocompromised conditions. Candidiasis is a common fungal disease found in humans affecting mucosa, skin, nails, and internal organs of the body. Candida albicans is generally considered the major pathogen among the Candida species. An increase in the prevalence of non-albicans species has been noted during the last decades. Aims and Objectives:The study was done to evaluate the performance of the conventional identification method and commercially available chromogenic Candida speciation media (CHROMagar) for the identification of medically important yeast and yeast-like organisms in a routine clinical microbiology laboratory. Materials and Methods: This study was conducted in the Department of Microbiology, Gandhi Medical College, Hamidia, and Associated Hospitals, Bhopal (M.P.), from January 2020 to October 2021. A total of 180 samples were collected from patients suspected of superficial mycoses which were then subjected to direct KOH examination and culture on plain Sabouraud’s dextrose agar (SDA), on SDA with antibiotics slants (cycloheximide and chloramphenicol). The growths were examined macroscopically as well as microscopically. Germ tube tests and inoculations on CHROMagar Candida medium were performed on all growths identified as yeasts and confirmed by morphology on CMA. Results: In our study, the majority of patients, belonged to the age group of 21–30 years (25%) with a male-to-female ratio of 2:1. Candida tropicalis (44.68%) was the most common Candida species, followed by C. albicans (38.30%), Candida krusei (12.77%), and Candida glabrata (4.25%). Conclusion: Along with C. albicans, non-albicans Candida spp such as C. tropicalis, C. krusei, and C. glabrata are increasingly being isolated from clinical specimens. Identification of Candida species by colony color on Hicrome correlated with the morphology on CMA. Thus, the incorporation of CMA in routine yeast identification is more judicious than Hicrome as it increases the accuracy in the identification of Candida species within the same time as that of Hicrome.